Analisis Rasio Keuangan untuk Menilai Kinerja Keuangan pada Credit Union Bahtera Sejahtera Maumere - Maria Ernista Sika; Andreas Rengga; Elisabet Luju (Prosiding Seminar Nasional Ilmu Manajemen Kewirausahaan dan Bisnis, 2024)
The background of this research was the importance of assesing the financial performance of cooeratives as an evaluation for the company’s future development. This research aimed to determine the condition of the financial performance pf the Bahtera Sejahtera Credit Union based on the indicators of Liquidity Ratio, Solvency Ratio, and Profitability Ratio. The populatiom and samples in this research were the data from the financial statements of the Bahtera Sejahtera Credit Union from 2017-2021. The research type was descriptive with a quantitative approach. The findings showed that the financial performance of the Bahtera Sejahtera Maumere Credit Union in 2017-2021 according to the Regulation of the Minister of Cooperatives and Small and Medium Enterprises of the Republic of Indonesia No.06/per/M.KUKM/V/2006 for the Liquidity Ratio (Current Ratio) was at bad criteria with an average yield of 121.00% based on the the standards set, namely <125%->135%. The Solvency Ratio (Total Debt To Total Assets) was in the unfavorable criteria with an average value of 76.37% based on the established standard of 60%-80%, and (Total Debt To Equity) was in the bad criteria with results the average was 328.03% based on the established standard of >200%, while the profitability ratio (Return On Assets) is in the unfavorable criteria with an average value of 1.20% based on established standard of 1%-3%, and (Return On Equity) were in the unfavorable criteria with an average value of 5.24% based on established standard of 3%-<9%.